Using Simulated Handover to Assess Team-Based Competencies in a Virtual Environment. Issue 1 (June 2021) - Sadighi, Mozhdeh; Lazzara, Elizabeth H.; Michael, Meghan; Hernandez, Jessica; Chan, Chrissy; Shields, Ian H.; Preble, Richard; Phelps, Mary E.; Tannenbaum, Scott; Greilich, Philip
We utilized simulated patient scenarios in a virtual environment to improve students' communication skills during handovers. To determine how students performed during the scenarios, we assessed several behaviors: structured communication, closed-loop communication, and asking clarification questions. Results revealed that the students' performance was stronger in the first area (structure communication) and weaker in the second (closed-loop communication) and third (asking clarifying questions) areas.